2021
DOI: 10.1002/advs.202100786
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Exciton–Phonon Coupling to Achieve a Near‐Unity Photoluminescence Quantum Yield in One‐Dimensional Hybrid Metal Halides

Abstract: Low-dimensional hybrid metal halides are emerging as a highly promising class of single-component white-emitting materials for their unique broadband emission from self-trapped excitons (STEs). Despite substantial progress in the development of these metal halides, many challenges remain to be addressed to obtain a better fundamental understanding of the structure-property relationship and realize the full potentials of this class of materials. Here, via pressure regulation, a near 100% photoluminescence quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 39 publications
1
50
0
Order By: Relevance
“…The analysis results of the theoretical calculation demonstrated that, at the low-pressure region, all octahedra exhibited a persistent shrinking, resulting in the continuous cell contraction. The reduction of exciton–phonon coupling strength can also be attributed to the shrinkage of octahedra upon compression, which strengthens the metal–halogen bond energy of and weakens the deformability of the lattice. The attenuated electron–phonon coupling strength would decrease the STE bind energy owing to the detrapping of STEs. Eventually, the intensity of both NE and BE decreased under much higher pressure .…”
Section: Resultsmentioning
confidence: 99%
“…The analysis results of the theoretical calculation demonstrated that, at the low-pressure region, all octahedra exhibited a persistent shrinking, resulting in the continuous cell contraction. The reduction of exciton–phonon coupling strength can also be attributed to the shrinkage of octahedra upon compression, which strengthens the metal–halogen bond energy of and weakens the deformability of the lattice. The attenuated electron–phonon coupling strength would decrease the STE bind energy owing to the detrapping of STEs. Eventually, the intensity of both NE and BE decreased under much higher pressure .…”
Section: Resultsmentioning
confidence: 99%
“…Broadband STE emissions of low-dimensional metal halides were first reported in 2D layered Pb–Cl and Pb–Br perovskites by Dohner et al in 2014, , largely triggering the boom of this sort of materials, while at that time the luminescence of analogous Pb–I slabs was commonly dominated by a narrowband free exciton (FE) emission. , Subsequently, it was found that STE and FE emissions can coexist in 1D or 2D lead iodides, in which the former is usually weaker than the latter. ,, In contrast to 2D counterparts, 1D lead-based hybrid systems with unique core–shell quantum wire structures hold greater structural adjustability and tunable photoluminescence (PL) properties. For instance, the corrugated 1D structure based on double-edge-shared octahedral PbBr 6 2– units , shows an initial PL quantum yield (PLQY) of 10%, which is significantly elevated to 100% at a pressure of 3 GPa . In addition, the 1D postperovskite type chains constructed by the corner-sharing dimers with edge-sharing PbX 6 (X = Cl, Br, and I) octahedra show tunable, broadband luminescence properties , and high PLQY (60%); in such a nice system, the nature of halogen significantly governs the intensity of the resulting broadband emission through tuning the excitonic self-trapping depth (Cl > Br > I) .…”
mentioning
confidence: 98%
“…20,21,23 In contrast to 2D counterparts, 1D lead-based hybrid systems with unique core−shell quantum wire structures hold greater structural adjustability and tunable photoluminescence (PL) properties. 24−30 For instance, the corrugated 1D structure based on double-edge-shared octahedral PbBr 6 2− units 24,31 shows an initial PL quantum yield (PLQY) of 10%, which is significantly elevated to 100% at a pressure of 3 GPa. 31 In addition, the 1D postperovskite type chains constructed by the corner-sharing dimers with edge-sharing PbX 6 (X = Cl, Br, and I) octahedra show tunable, broadband luminescence properties 21,32 and high PLQY (60%); 33 in such a nice system, the nature of halogen significantly governs the intensity of the resulting broadband emission through tuning the excitonic self-trapping depth (Cl > Br > I).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative thermodynamic parameter, pressure can effectively modify the local structure and coordination, and further achieve modification of LPEs [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In this work, by using high pressure to modulate the local structure of SbSI, the stereochemical role of LPEs is controllably manipulated towards designable optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%